Impact of Chokeberry (Aronia melanocarpa L.) Extracts on the Physicochemical Properties of Wheat Bread - Adamczyk, Greta; Posadzka-Siupik, Zuzanna; Bobel (Zinchenko), Inna; Kowalczewski, Przemysław Łukasz; Szwengiel, Artur (My University, 2025)
Chokeberry (Aronia melanocarpa L.) is a valuable raw material rich in health-promoting compounds, including anthocyanins, making it an excellent ingredient in food such as bread. In this research, water in the bread recipe was substituted with chokeberry extract (ChE). Dried chokeberry powder was used to obtain extracts with 0 and 7.5 Brix content. Two types of water chokeberry extracts (0 and 7.5 Brix ChE) were applied in the wheat bread recipe with doses of 10, 15, 20, and 30% (m/m), replacing water, respectively. The obtained chokeberry extract contributed to the enrichment of the bread in total polyphenol content and the antioxidant capacity. The control bread sample (i.e., without the extract) had a total polyphenol content (TPC) of 25.706 mgGAE/100 g, while the bread samples with the extract had TPC values ranging from 29.037 to 45.282 mgGAE/100 g. At the same time, adding chokeberry extract to the bread matrix contributed to increasing the antioxidant capacity. Bread with ChE was characterized by the same dough yield and loaf volume of bread compared to the control sample, but with changed oven loss, total baking loss, bread yield, specific volume, bread acidity and porosity of the crumb. However, there was no statistically significant effect on the chewiness and cohesiveness of the crumb in the sample texture (α=0.05). A small effect of anthocyanins on the color of bread was observed, and sugars played the dominant role in the tested samples. Chokeberry in the form of an aqueous extract added to wheat bread can be an excellent ingredient in bread. Чорноплідна горобина (Aronia melanocarpa L.) – цінна сировина, багата на корисні для здоров'я сполуки, включаючи антоціани, що робить її чудовим інгредієнтом у таких продуктах, як хліб. У цьому дослідженні воду в рецепті хліба було замінено екстрактом чорноплідної горобини (ХЕ). Для отримання екстрактів з вмістом 0 та 7,5 Brix використовували сушений порошок чорноплідної горобини. У рецепті пшеничного хліба було застосовано два типи водних екстрактів чорноплідної горобини (ХЕ 0 та 7,5 Brix) у дозах 10, 15, 20 та 30% (м/м), які замінили воду відповідно. Отриманий екстракт чорноплідної горобини сприяв збагаченню хліба загальним вмістом поліфенолів та антиоксидантною здатністю. Контрольний зразок хліба (тобто без екстракту) мав загальний вміст поліфенолів (ЗВП) 25,706 мгГАЕ/100 г, тоді як зразки хліба з екстрактом мали значення ЗВП від 29,037 до 45,282 мгГАЕ/100 г. Водночас додавання екстракту аронії до матриці хліба сприяло збільшенню антиоксидантної здатності. Хліб з ХЕ характеризувався таким самим виходом тіста та об'ємом буханця хліба порівняно з контрольним зразком, але зі зміненими втратами в печі, загальними втратами при випіканні, виходом хліба, питомим об'ємом, кислотністю хліба та пористістю м'якушки. Однак статистично значущого впливу на жувальну здатність та когезивність м'якушки в текстурі зразка не спостерігалося (α=0,05). Спостерігався невеликий вплив антоціанів на колір хліба, а цукри відігравали домінуючу роль у тестованих зразках. Аронія у вигляді водного екстракту, що додається до пшеничного хліба, може бути чудовим інгредієнтом у хлібі.
Keywords: кафедра технології хлібопекарських і кондитерських виробів; wheat bread; black chokeberry; polyphenols; пшеничний хліб; чорноплідна горобина; поліфеноли